Dialética das relações sociais: o trabalho pedagógico dos(as) diretores(as) do Instituto Estadual de Educação Olavo Bilac, RS (1974-2015) - Vedoin, Andreia (2018)
This research is part of the Research Line LP2- School Practices and Public Policies of the Program and Post-Graduation in Education of the Education Center of the Federal University of Santa Maria. The general objective was to analyze the speeches of the IEEOB directors in order to understand the extent to which they demonstrate the implications and reciprocities between their pedagogical work and the social relations established by them, considering the period from 1974 to 2017.From the perspective of historical-dialectical materialism, a qualitative research was developed, in which, participated, the directors of the Olavo Bilac State Education Institute, Santa Maria, RS, who held the position in the period from 1974 to 2017.The process of data production took place through some Brazilian educational legislation and the Olavo Bilac Historical Collection documents, interviews and field notes. The interviews, after transcribed, were analyzed, as well as, the field notes, some Brazilian educational legislation and the Olavo Bilac Historical Collection documents.In the analysis of the data, we considered the categories of the Marxist method, namely: totality, historicity, contradiction and praxis. In the historicity of the IEEOB,it was found,that the directors occupied a central place, not only in the Institute, but also in the society of Santa Maria, (re) producing power relations.In this sense, it was observed that the pedagogical work of some directors was constructed by determinations of the public policies or by political interests of those who indicated him/herto the position of director, but it was also constructed by the social relations established by them.In this research, the following thesis is defended: the pedagogical work of the directors is based on the social relations established by them throughout life and from the capitalist mode of production.In the opposite movement, these social relations are impacted by their pedagogical work, by their way of producing material life, thus producing a dialectical relationship between the pedagogical work of the directors and the social relations contracted by them in a movement between the individual and the social.In capitalist society, these social relations produced in the work have an alienating and hostile character, are, for the most part, relations of conflicts and disputes. However, while historically committed to the dominant social class, education is capable of producing contradictory relationships.Therefore, from the critical pedagogical work of school principals, it is possible to create times and spaces for overcoming social relations of submission and domination.In addition, the pedagogical work of school principals, as it is constituted by the social and political dimension, that are fundamental elements for the formation of critical consciousness, can contribute to social praxis.